Level of commitment among the employees of the local government unit of Mayorga, Leyte. - Gallaron, Jovelyn (Jovelyn Gallaron, 2010)
Mayorga is a fifth class municipality in the Province of Leyte. The researches were interested in finding out the extent to which employees of the said municipality perceived their own level of commitment while household heads served as inter-raters. Employee commitment refers to the psychological bond of an employee to an organization, the strength of which depends on the degree of employee involvement, employee loyalty, and belief in the values of the organization. The study also identified the socio-economic and demographic characteristics of these employees and their relationship with the level of bureaucratic idealism.